This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: (18) ( t ) y + 2 t y = ( t ) sin t t (19) d dt ( ( t ) y ) = ( t ) sin t t ( t ) = t 2 (20) d dt ( t 2 y ) = t sin t (21) Z d dt ( t 2 y ) dt = Z t sin t dt (22) t 2 y =-t cos t + Z cos t dt, ( integration by parts ) (23) =-t cos t + sin t + c (24) y = t-2 (-t cos t + sin t + c ) , y ( / 2) = 1 c = 2 4-1 (25) y = t-2 -t cos t + sin t + 2 4-1 (26) 2...
View Full Document
This note was uploaded on 01/21/2011 for the course MATH 2930 taught by Professor Terrell,r during the Spring '07 term at Cornell University (Engineering School).
- Spring '07